Urban acupuncture - Lerner, Jaime, 1937-; Margolis, Mac; Muello, Peter; Daher, Ariadne (Washington [D.C.] : Island Press, 2014)
'As Mayor of Curitiba, Brazil, architect and urbanist Jaime Lerner transformed his city into a global model of sustainability and livability. During more than forty years of innovation in cities, he has learned that changes do not need to be large-scale and expensive to transform -- one block, park, or person can have an outsized effect on life in the surrounding city.'--Provided by publisher.
Collection of short essays and poems on different aspects of city life and city planning.
'This is not a technical or theoretical book; it is a book filled with poetry and magic that communicates the importance of dreaming and, at the same time, being pragmatic and making things happen; to always ask if we have the right solution or if there is a better, maybe a simpler way.'--Foreword.
Translated from the Portuguese.
Keywords: Urban renewal; Civic improvement; Civic improvement -- Brazil; City planning